Types and density of bivalve in themangrove ecosystem of the Sungai Asam Village Reteh Sub-districtIndragiri Hilir Regency Riau Province - Hutri Aliva; Adriman Adriman; Nur El Fajri (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
Abstract Bivalva is a types of aquatic organism that lives in mangrove ecosystems.                             This research aims to determine the types and density of bivalve in the mangrove ecosystem of Sungai Asam Village. The research has been conducted on July to August 2020. There were 3 stations set, St1 is a mangrove forest area that is relatively natural and far from residential area, St2 was in the mangrove forestwhich is used as a tourist destination and St3 was in the mangrove forest that has residential area. Each station 3 plots/station and 3 subplots/plot. In each subplot (1x1m2), the bivalve were collected by hand. Results shown that there were 3 species of bivalve, namely Polymesoda erosa, Geloina expansa, Pharella acutidents with density was  6.296-41.852 organisms/ha. The density of mangrove trees in Sungai Asam Village is categorized as damaged. There is a close relationship between mangrove tree and bivalve densities. Keyword : Aquatic organisms, Geloina expansa, Mangrove forests,Pharella acutidents, Polymesoda erosa